IDENTIFICATION OF SUSPECTED PALEOTSUNAMI DEPOSITS STUDY FROM KARAPYAK BEACH, PANGANDARAN AREA, WEST JAWA, INDONESIA - Aswan ⠀; Yan Rizal (BULLETIN OF THE MARINE GEOLOGY, 2021)
Identifying and determining paleotsunami deposits can be a vital tool for establishing the periodicity of earthquakes and their associated tsunami events beyond historical records. However, their deposits can be difficult to establish and to date. In this study, we used the characteristics of the 2006 Pangandaran tsunami deposit as a reference to identify paleotsunami deposits in Karapyak Beach, Pangandaran area, West Java, Indonesia. Similar to the 2006 Pangandaran tsunami deposit, the Karapyak Beach paleotsunami deposit is characterized by light brown loose sand materials overlying a dark brown paleosol layer with erosional contact. A thin layer of tsunami deposit, although varies in thickness, is locally found just above erosional contact. The deposit reveals non-laminated coarse grain size in the lower part that gradually changes into medium to fine sand in the upper part. The base of this lower part is rich with broken mollusc shells and corals. The mid to top of the lower part may contain several still-intact mollusc shells and corals, rock fragments, and anthropogenic products (roof tiles). Those types of fragments are absent in the upper part of this thin tsunami deposit. Grain size analysis shows a mixture of fine and coarse grains in the lower part of the 2006 tsunami deposits, as well as in the suspected paleotsunami deposits, suggesting an uprush of high energy flow during the sedimentation. The fining upward sequence above the mixed grain layers reflects a waning flow in pre-backwash deposition. Foraminifera analysis also shows a mixture of shallow and deep marine foraminifera in both recent tsunami and paleotsunami deposits. Based on the characteristics of the 2006 tsunami deposits, there are at least four paleotsunami deposits identified in Karapyak Beach, Pangandaran area.